2021
DOI: 10.3389/fmolb.2021.801577
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Influence of K280 Acetylation on the Conformational Features of Tau Core Fragment: A Molecular Dynamics Simulation Study

Abstract: Abnormal aggregation of the microtubule-associated protein Tau is closely associated with tauopathies, including Alzheimer’s disease and chronic traumatic encephalopathy. The hexapeptide 275VQIINK280 (PHF6*), a fibril-nucleating core motif of Tau, has been shown to play a vital role in the aggregation of Tau. Mounting experiment evidence demonstrated the acetylation of a single-lysine residue K280 in the PHF6* was a critical event for the formation of pathological Tau amyloid deposits. However, the underlying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 57 publications
(64 reference statements)
0
13
0
Order By: Relevance
“…To study the self-aggregation of PHF6 peptides and phosphorylated PHF6, we simulated two different systems: the wild-type PHF6 system (named PHF6 system) and the Y310 phosphorylated system (named Pho-PHF6 system). The amino acid sequence of PHF6 is 306 VQIVYK 311 , capped by the ACE (CH 3 CO) group at the N-terminus and the NH 2 group at the C-terminus as determined computationally 44 and experimentally. 45 We first constructed the fully extended peptide using the PyMol program and then performed a 50 ns MD simulation at 450 K in water to generate the initial coil conformations.…”
Section: ■ Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To study the self-aggregation of PHF6 peptides and phosphorylated PHF6, we simulated two different systems: the wild-type PHF6 system (named PHF6 system) and the Y310 phosphorylated system (named Pho-PHF6 system). The amino acid sequence of PHF6 is 306 VQIVYK 311 , capped by the ACE (CH 3 CO) group at the N-terminus and the NH 2 group at the C-terminus as determined computationally 44 and experimentally. 45 We first constructed the fully extended peptide using the PyMol program and then performed a 50 ns MD simulation at 450 K in water to generate the initial coil conformations.…”
Section: ■ Methodsmentioning
confidence: 99%
“…The MD simulation study on the tau K254–K290 fragment revealed that the complex with three phosphorylated sites (Ser262, 285, and 289) could form compact and more stable structures than that with one phosphorylated site (Ser262) . Our previous work investigated the influence of acetylation of K280 on the aggregation of PHF6* by performing REMD simulations and found that K280 acetylation strengthened the intermolecular interactions and led to more ordered β-sheet-rich structures . In this study, we focused on the early aggregation process of PHF6 peptides and explored the potential effect of the phosphorylation of Y310 on the PHF6 oligomerization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, a contact is formed when the aliphatic carbon atoms of two atom sets come within 0.54 nm or any other atoms of two atom sets lie within 0.46 nm. 48,49 Two aromatic rings are considered to form p-p stacking when their centroid distance is within 0.65 nm. 50 We defined a cation-p interaction if the distance between the N atom in an NH 3 + group and the centroid of an aromatic ring is less than 0.6 nm.…”
Section: Analysis Methodsmentioning
confidence: 99%
“…70,71 It is suitable for studying the structural characteristics of intrinsically disordered protein (IDP) like Tau. In recent years, several computational studies utilize the advanced sampling methods to characterize the structural features and conformational properties of Tau, 48,72,73 which provide a comprehensive understanding of Tau aggregation at the atomic level. This journal is © the Owner Societies 2022…”
Section: Dominant Binding Sites and Different Disruptive Modes Of Cur...mentioning
confidence: 99%